NSR Skirt Marketing Communication Strategy Planning In Building Awareness Through Social Media Marketing - Nur Sella Rakhmadhona (Universitas Muhammadiyah Makassar, 2022)
The phenomenon of online marketing is growing along with the growth of internet penetration in Indonesia. A more visible impact is the use of internet services with social media networks which add a new dimension to disseminating messages, exchanging information about products and also experiences with a brand. Seeing this opportunity, NSR uses the concept of marketing through social media marketing, the problem is that many do not know about the existence of the NSR brand. Therefore, the SOSTAC model of marketing communication strategy is used through social media, as a supporter of planning to build awareness first. Marketing strategy planning in building awareness is designed to be implemented over a period of six months. Several elements that become criteria for achieving awareness goals using social media are the number of likes, followers, hashtags and viewers followed by an increase in purchases